Theology towards the Problem of the Existence of Extraterrestrial Civilizations - Pabjan, Tadeusz (Studia Warmińskie, 2024)
The hypothetical existence of extraterrestrial civilizations is an issue that has been studied by representatives of natural sciences for a long time. The high probability that there are other – apart from Earth’s inhabitants – intelligent beings in the universe resulted in a large-scale search for scientific evidence for the existence of aliens, which began in the mid-20th century. These searches did not bring the expected results: scientists failed to confirm the existence of extraterrestrial civilizations or establish contact with their representatives. What is the theological interpretation of this issue? Are the current failures in the scientific search for intelligent life in space a sufficient reason to completely ignore the possibility of the existence of "other children of God" in theological analyses? The article is an attempt to answer these questions. It presents arguments that taking up this issue is beneficial for theology for many reasons, and that this problem should not be omitted within this discipline. Several specific issues that arise in this context and require theological reflection are also indicated (e.g. the problem of the salvation of aliens and the hypothesis of the re-incarnation of God on one of the extrasolar planets).